THE EFFECT OF VISUAL SOURCES AND TIME PRESSURE ON ENVIRONMENTAL PERCEPTION AND ATTRACTIVENESS THROUGH THE ADVERTISEMENT - Tran, Nhu-Y; LeÃ³n, IvÃ¡n Alvarez (THE Journal : Tourism and Hospitality Essentials Journal, 2019)
The main objective of this study was to capture and analyses the role of visual resources and time pressure as they affect customer behaviour in the hospitality industry. This study examined effective reactions on booking time and type based on vacation advertisements. The research method had a 3 x2 within-subjects design with 6 experimental conditions obtained by crossing the levels of two independent variables: 1) Time pressure (i.e., exact date, number of days left and counting-down timing); 2) Visual source (i.e., video and picture). The study designed a self-report questionnaire based on 8 socio-demographic items and three conceptual elements, such as the facility quality, environmental features and promotional attractiveness. This research provided data regarding the differences in visual source and time pressure in marketing promotion. It showed that videos had more impact on customer perceptions regarding the facility quality and environmental features. The study outlines the value of marketing strategies in building content and successful design in differentiating a resort from the competition and offering a positive experience (low investment yielding high return) for millennial.